Singing Nuns and Soft Power: British Diplomats as Music Tourists in Seicento Venice - Mailes, Alana (Religions, 2022)
Historians of early modern statecraft and confessional politics have traditionally treated the arts as peripheral to the more official bureaucratic concerns of government agents. Meanwhile, musicological scholarship rarely centers the experiences and exploits of politicians who participated in early modern musical events. This case study on British envoys to Venice in the early Stuart period illustrates how musical activity and political work were, in fact, thoroughly imbricated within the daily mechanics of cross-confessional ambassadorship. Drawing on seventeenth-century diplomatic sources, I detail how both English and Northern Italian politicians made strategic use of sacred music-making—particularly vocal performance in local nunneries—to influence their dealings with foreign states, as well as how English diplomats in the Italian peninsula surveilled Catholic musical devotions in their covert correspondences to communicate information about international affairs. In revealing these moments of interconnection between music, religion, and geopolitics, I seek to further recent efforts in the New Diplomatic History to highlight the contributions of women and artistic practice within histories of international relations.